Implementation of Ecdis In Navigation In Traffic Separation Schemes (Tss): A Case Study On The Mv. Ocean Sukses - Raafid Yhuan Katulistiwa; Anugrah Nur Prasetyo; Dyah Ratnaningsih; Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The increasing density of shipping traffic in the Traffic Separation Scheme (TSS) requires the use of navigation technology that can improve shipping safety and efficiency. The Electronic Chart Display and Information System (ECDIS) is an electronic navigation system that plays an important role in supporting real-time shipping planning and monitoring. This study aims to analyze the application of ECDIS, evaluate the understanding of the officers regarding its use, and assess the effectiveness of ECDIS in improving navigation safety in the TSS on the MV. Ocean Sukses. The study used a qualitative descriptive approach. The study population was all officers involved in ship navigation, while the research sample consisted of the captain, Chief Officer, Second Officer, and Third Officer who were selected purposively. The research instruments included interview guidelines, observation sheets, and documentation. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that ECDIS was used optimally in route planning, ship position monitoring, safety alarm settings, and integration with AIS and radar during shipping in the TSS. In addition, most officers had a good understanding of the ECDIS features. The research conclusion shows that the implementation of ECDIS effectively improves navigation safety, situational awareness, and decision-making quality, although its effectiveness remains dependent on user competence and regular system updates.